Un poetico sonnambulismo e una folle passione per la follia La romantizzazione della medicina nell'opera di E.T.A. Hoffmann - Cora, Sieglinde (Premio Ricerca «Città di Firenze», 2013)
The work analyses the complex relationship between mental illnesses and curative medicine in the writings of E.T.A. Hoffmann, highlighting problems deriving from unsuitable practices, and shedding light on the overwhelming, asymmetric relationship between doctor/patient, man/woman. The work analyses the doubling phenomena arising from the diaries, which Hoffmann overcame determined not to fall into madness; moreover, the author highlights Hofmmann's qualities as a man and a scholar, attentive to the limits of therapies, questioning doctors without understanding. The author summarises Hoffmann's ideas on the libertarian approach to illness, which includes the acceptance of the patient in their whole being, and presents his idea of therapy consisting of interpersonal dialogue and of listening to a story which reflects a similar case. The author also suggests the novelty of the "talking cure" method ante litteram, which was then successfully adopted by psychoanalysis: a method full of ideas, fruitful for literature, from Poe to Schnitzler, and for cinema, from Hitchcock to Kubrick.